DARI UANG TUNAI KE KLIK: PENDEKATAN MOBILE UNTUK KEUANGAN INKLUSIF - Putri, Lidya Ayuni; Iqbal, Muhammad; Audrey, Relifidi; Hendrawaty, Ernie; Banuwa, Laili Fadhilla (Jurnal Bisnis dan Manajemen (JBM), 2026)
This conceptual study examines the transformative potential of mobile banking applications in promoting financial inclusion. It highlights the transition from cash-based transactions to digital financial services and their role in expanding access to financial products and services, particularly for underserved populations in Indonesia. The study employs a literature review approach by synthesizing previous research on financial inclusion, mobile banking, and the development of digital financial systems in Indonesia. The findings indicate that mobile-based financial services have significant potential to enhance financial inclusion. Innovations such as mobile wallets, peer-to-peer payment systems, and digital lending platforms enable broader access to savings, credit, and financial protection services for unbanked and underbanked communities. However, several challenges remain, including limited digital literacy, technological infrastructure constraints, and regulatory issues that require continuous improvement. This paper contributes conceptually to the growing body of literature on digital financial inclusion and provides a foundation for future empirical research. Furthermore, the findings offer important implications for policymakers, financial institutions, and digital service providers in their efforts to expand financial access and reduce the financial inclusion gap.